Assessment of genetic diversity in sunflower germplasm lines: Assessment of genetic diversity in sunflower germplasm lines - S B SAKHARE; RUPALI CHAKRABORTY; SANGITA FATAK; N J WANKHADE (Journal of Oilseeds Research, 2020)
The present study was undertaken to estimate the extent of genetic diversity among germplasm lines and to identify genetically diverse lines of sunflower for their further exploitation. Thirty- three genotypes were grouped into eight clusters by using Tocher’s method. On the basis of average inter cluster distance, cluster mean and mean performance of genotypes, 16 superior crosses have been suggested which are expected to yield desirable genetic gain in breeding programme.